PENGARUH COOPERATIF LEARNING BERBASIS VOICE NOTE TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS XI MIPA DI SMA NEGERI 3 BANTAENG - Haerul Mutiah; Ardianto A; Sarina S (Jurnal Pendidikan Sang Surya, 2021)
This study aims to examine how much influence the learning of Cooperative Learning based on Voice Note (Vn) on the learning outcames of biology students of class XI MIPA in SMA Negeri 3 Bantaeng. This study used an experimental method to form Pre-Experimental Design type one group pretest-posttest design. The sample in this study are 33 students. The calculation result obtained t test 19,488 while ttabel with dk = 33-1 = 32 and a significant level (alpha) = 0.05 is 1.694, turns thitung ttable or greater equal than 19,488 greater equal than 1.694, which means a significant influence on the application of Voice Note (Vn) based Cooperative Learning. From the result of the calculation of the Post Test average value of 81.61 and included in the high category. This means that Cooperative Learning based on Voice Note (Vn) has a high influence on the learning outcomes of biology XI MIPA at SMA N 3 Bantaeng.